Microtopography mediates the climate–growth relationship and growth resilience to drought of Pinus tabulaeformis plantation in the hilly site - Zhao, Hongming; Wu, Jiabing; Wang, Anzhi; Guan, Dexin; Liu, Yage (Frontiers in Plant Science, 2022)
Understanding the factors affecting the growth of plantation forests can reduce the loss of economic and ecological values caused by plantation forest subhealth. Plantation forests are widely distributed in hilly areas with microtopographic features. Microtopography influences climatic factors associated with plant growth, during not only general time but also extreme events like droughts. However, little research has been conducted on the effects of microtopography on the plantation forest growth. In this paper, we selected Pinus tabulaeformis planted in a hilly site, and studied the effect of microtopography on the climate–growth relationship and drought response of a typical plantation in Northeast China using dendroecological methods. We found: 1) Between hill positions, temperature caused a climatic growth difference. Compared to the hilltop, the correlation of annual growth on the hillside with monthly temperature was more negative in July–August and less positive in January–April. 2) Between aspects, precipitation intensities caused a climatic growth difference. Compared to the sunny slope, the correlation of annual growth on the shady slope with monthly total precipitation below 10 mm/day was less positive (May–June) or more negative (March–April and July), while that with monthly total precipitation above 10 mm/day was more positive in most months.3) Drought response varied significantly based on hill position and aspect. There was no significant difference in resistance between hill positions, while recovery and resilience on the hilltop were greater than those on the hillside.Resistance, recovery, and resilience were all lower on the sunny slope than those on the shady slope. Overall, microtopography exists the effects on the growth of plantation forests, both in terms of climate-growth relationships in general climate and in response to drought when extreme events. Meanwhile, the climatic factors that caused the difference in growth of plantation forests between hill positions and aspects differed. The difference in growth between hill positions was caused by temperature, while that between aspects was caused by precipitation intensity. Drought response difference reflected the legacy effect of drought on plantation growth, which could lead to subsequent changes in climate-growth relationships. These findings demonstrate that strengthening the research of forest trees on microtopography is necessary for accurate carbon sink assessment and precise forest management.